SEDIMENTOLOGI DAN STRATIGRAFI ALUVIUM BAWAH PERMUKAAN DI PESISIR CIREBON DAN SEKITARNYA - Suyatman Hidayat; Herman Mulyana; Herman Moechtar; Subiyanto Subiyanto (Pusat Survei Geologi, 2009)
This study was based on sedimentological analyses of seven boreholes located along the NW to SE traverse, approximately parallel to coastal line of Cirebon. The penetration of the bore head varies from 8 to 13 m. Holocene subsurface of alluvial deposits can be divided into seven environment systems, consisting of Gintung Formation and deposits of offshore, nearshore, beach sand, swamp, channel river, and floodplain. Based on stratigraphic aspects, the succession of that sediments can be divided into three sedimentary intervals (IP I-III). Each interval is typically for environment changes which is controlled by changes of sea level, such as high sea level (IP I), sea level falling (IP II), and low sea level (IP III). The Quaternary dynamics related to environment changes and changes of basin fill were influenced by universal of climatic circulation, regional tectonic, and local of sea level changes.Â Keywords: Aluvium deposits, sea level, tectonic, climate